(3HQfGeL Sdhcj bGFe Ydi GdRjGOI GdJOQjLjI aj Whd GdcdGe hJYbjOg hCKQg Ydi NaV MOI GddLdLI hJMSjf eSJhi GdJMUjd GdOQGSj (B= s Behavioral Program based on the Gradual Increase in Length and Complexity of Utterance and its Impact on the Reduction of Stuttering and Improve the Level of Academic Achievement - (3jGSQ YHOGdMejO eMehO CMeOs; (3SejQI CHhGdMSf YHOGdSdGe GdfLGQ (B: s; (3efGd efUhQ GdMedGhi (B: s ((3GdbGgQI (B: s (3jGSQ YHOGdMejO eMehO CMeO (B: s, 2014)
(3gOa GdHMK GdMGdj Edi NaV MOI GddLdLI dOi GdCWaGd GdeJdLdLjf aj eQMdI GdeOQSI hCjVkG JMSjf eSJhi JMUjdge GdOQGSj ef NdGd HQfGeL Sdhcj bGFe Ydi GdRjGOI GdJOQjLjI aj Whd GdcdGe hJYbjOg, hGSJNOeJ GdOQGSI GdCOhGJ GdBJjI(B:(3GNJHGQ GdeUahaGJ GdeJJGHYI Gdedhf (B((3EYOGO QGajf, (B1990), (3hebjGS GdeSJhi GdGLJeGYj GdGbJUGOj ddCSQI (B((3EYOGO YHO GdYRjR GdTNU(B: 2006), (3hCOGI bjGS TOI GddLdLI ddCWaGd hGdeQGgbjf (B((3EYOGO SjO GdHgGU, (B2005), (3hGNJHGQGJ GdJMUjd GdOQGSj, hHQfGeL GdRjGOI GdJOQjLjI aj Whd GdcdGe hJYbjOg (B((3EYOGO GdHGMK(B)(3, hJchfJ YjfI GdOQGSI ef (B(20) (3Wad hWadI ef GdedJMbjf HGdeQMdI GdGHJOGFjI hGdPjf jYGfhf ef GddLdLIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ h GdHMhK GdJQHhjI (B- (3bSe GdGQTGO GdfaSi h GdJQHhis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJMUjd GdOQGSjs; (3GdRjGOI GdJOQjLjI aj Whd GdcdGe hJYbjOgs; (3GddLdLIs